2014
DOI: 10.1111/clr.12533
|View full text |Cite
|
Sign up to set email alerts
|

Sequential healing at implants installed immediately into extraction sockets. An experimental study in dogs

Abstract: Similar patterns of sequential osseointegration were found at implants installed in healed alveolar bone or in alveolar sockets immediately after tooth extraction. The coronal termination level of osseointegration, that was different after 1 week, was found similar at the 3-month observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Based on previous evidence, the influence of the following factors on osseointegration surrogate outcomes (%BA, %BIC) was analysed herein: defect morphology/dimensions (Polyzois et al, ; Schwarz et al, ), implant placement time (Mainetti et al, ), implant surface characteristics (Barfeie et al, ) and the use of membranes to contain the grafted sites (Chiapasco and Zaniboni, ; Lorenzoni et al, ). Only the timing of implant placement demonstrated a statistically significant effect on %BIC, with 11% greater BIC observed in implants placed in association with defects surgically created in healed sites compared with the BIC in immediate implants placed in large extraction sockets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous evidence, the influence of the following factors on osseointegration surrogate outcomes (%BA, %BIC) was analysed herein: defect morphology/dimensions (Polyzois et al, ; Schwarz et al, ), implant placement time (Mainetti et al, ), implant surface characteristics (Barfeie et al, ) and the use of membranes to contain the grafted sites (Chiapasco and Zaniboni, ; Lorenzoni et al, ). Only the timing of implant placement demonstrated a statistically significant effect on %BIC, with 11% greater BIC observed in implants placed in association with defects surgically created in healed sites compared with the BIC in immediate implants placed in large extraction sockets.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relatively small number of studies and large heterogeneity in the current meta‐analysis complicate the interpretation of this finding. In context, a recent study reported similar sequential healing patterns around implants placed in extraction sockets vs. healed sites in dogs, with no significant differences in BIC at early (1 week) or later (3 months) time points (Mainetti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…, ; Mainetti et al. , ), one at implants installed in the rabbit tibiae (Caneva et al. ), and two at implants installed in humans (Bosshardt et al.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies included data from implants installed in either healed sites or extraction sockets (Mainetti et al. , ). In one of these studies, both implants were immediately loaded (Mainetti et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation